Histoenzymological study on circumvallate papilla and Von Ebner's gland in the tongue of castrated donkey - ROY, K S; SINGH, H; SINGH, JASWANT (The Indian Journal of Animal Sciences, 2013)
Histoenzymic study was conducted on tongue of 3 castrated donkey. The epithelium of tongue, vallate papillae taste bud. Von-Ebner's gland showed a variation in the activity of AKPase. ACPase, ATPase. SOH, LDH, GDH, NADPI-I. G6PD. MAO and CYO. ACHase was mainly seen in the neuronal elements and secretary cells. Sudanophilic lipid droplets were also localised in the vallate papillae and von Ebner'S gland.